Heart Rate Variability in Elite International ITF Junior Davis Cup Tennis Players - Santos Villafaina; Miguel Crespo; Rafael Martínez-Gallego; Juan Pedro Fuentes-García (Biology, 2022)
The aim of the present study was to investigate the evolution of the HRV during an international team tennis tournament in elite junior tennis players. A total of 11 tennis players, with a mean age of 15.36 (0.67) from six nationalities, participated in this cross-sectional study. Participants were measured one day before the event, before the first match, and before the second match of the ITF Junior Davis Cup event. Each of the registers lasted 5 min and the time domain, frequency domain and non-linear variables were extracted. The tournament took place in Valencia (Spain). Results showed that there was not a significant decrease in the heart rate variability (HRV) induced by precompetitive stress. However, significant differences (p-value < 0.05) were found between baseline and second match pre-competition HRV values in low frequency (LFNu) (p-value = 0.008) and high frequency (HFNu) power (p-value = 0.008), LF/HF ratio (p-value = 0.008) and Sample Entropy (SampEn) (p-value = 0.033) variables. Furthermore, cognitive anxiety (measured by CSAI-2r) (p-value = 0.017) and anxiety (measured by STAI-S) (p-value = 0.042) were higher before the first match than before the second match. Coaches and physical trainers could use HRV to control and manage the precompetitive anxiety of junior tennis players. The experience in international tournaments and the familiarization with the environment in the second match could explain these results.